The Impact of Using ChatGPT and Grammarly on developing Iraqi EFL University Students' Academic Essay Writing - اسوان جاسم (مجلة ابحاث ميسان, 2025)
Academic writing remains a significant challenge for Iraqi EFL (English as a Foreign Language) students due to limited exposure to authentic English contexts and a lack of structured writing practice. Though, for these types of challenges, the results of baring of exposure authentic English contexts and forms of writing practice have not appeared properly at their best. This case study evaluates the general effectiveness of using ChatGPT and Grammarly, which are AI-based writing assistants, for the English as Foreign Language Iraqi undergraduate students to improve academic writing. The study was carried out on 30 second-year students in the Department of English and involved a semester-long program on the use of ChatGPT, such as for idea generation and text expansion and feedback improving, and Grammarly to correct grammar and improve style. As to research methodology, this combined both quantitative and qualitative methods where pre- and post-tests were administered with a student survey and instructor interviews to examine the improvement of coherence, cohesion, grammatical accuracy, and academic style. Results indicate students improved considerably in composing structured writing of their essays-stringent grammar errors, and they are developing a more formal academic tone. Qualitative feedback also highlighted other new trends, such as the rise of student confidence and autonomy in writing. However, several adverse influences have been given, such as overreliance on the generation of AI-written content and failure in critical engagement with the feedback. Importantly, the findings indicated that AI tools could be supplementary supplementary materials for Iraqi EFL learners to be applied with direct writing instructions and critical thought strategies. This research contribution would supplement the increasing work done on AI-assisted language learning, with the additional dimension of applicability added for EFL teachers in Iraq, looking for novel ways to improve academic writing proficiency in students.